PENGARUH PROFITABILITAS DAN CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE (Studi Empiris pada Manufaktur yang terdaftar di Bursa Efek Indonesia tahun 2012-2016) - Ahmad Bukhori Muslim; Nengzih Nengzih (Jurnal Akuntansi Bisnis Pelita Bangsa, 2020)
The purpose of this study is to examine the effect of profitability and corporate governance on tax avoidance at manufacturing companies listed in Indonesia Stock Exchange 2012-2016. Data analysis technique used is multiple regression. The population in this study amounted to 18 manufacturing companies listed on the Indonesia Stock Exchange with the annual report period used in research in 2012 until 2016. Total samples used in research using purposive sampling as many as 90 manufacturing companies that have met the study criteria of the total population. Data collection is done by downloading the annual report data on the official website of Indonesia Stock Exchange which is www.idx.co.id and the site of each company. The results of this study show that (1) profitability has a significant negative effect on tax avoidance, (2) the composition of board of commissioners, managerial ownership, and institutional ownership have no significant effect on tax avoidance. Keywords: profitability, corporate governance, board composition, managerial ownership, institutional ownership, tax avoidance.